Flow Electrode Capacitive Deionization System with Simultaneous Desalting of Na+ and Gathering of Na - Yang, Ze-Qin (Langmuir : the ACS journal of surfaces and colloids, 2022)
Oceans contain many freshwater resources and metal elements that people need, so the rational development of marine resources can solve the two major problems of shortage of freshwater resources and metal elements for people. To solve these two challenges, a system was designed to obtain freshwater resources and metallic elements simultaneously. An ion enrichment module was added to the conventional flow capacitor deionization system to collect metal elements while the seawater was deionized. A flowing electrode allows the metal elements to enter the flowing electrode through the desalination ability. It transports the metal elements to the enrichment module through the fluidity of the fluid while reducing the ion concentration at the flowing electrode, thus reducing the effect caused by the rejection of the same ion and collecting and enriching the metal elements. We purchased activated carbon to test the feasibility of the system with different mass fractions of activated carbon suspensions. The results showed that the elemental enrichment capacity of the system increased from 12.291 to 14.795 mg, and the enrichment rate increased from 13.536 to 16.294 mg cm-2 h-1 as the mass fraction of activated carbon increased. Thus, the system accomplished the goals of desalination and metal collection simultaneously